2017
DOI: 10.3847/1538-4357/aa73df
|View full text |Cite
|
Sign up to set email alerts
|

The NANOGrav Nine-year Data Set: Measurement and Analysis of Variations in Dispersion Measures

Abstract: We analyze dispersion measure (DM) variations of 37 millisecond pulsars in the nine-year North American Nanohertz Observatory for Gravitational Waves (NANOGrav) data release and constrain the sources of these variations. DM variations can result from a changing distance between Earth and the pulsar, inhomogeneities in the interstellar medium, and solar effects. Variations are significant for nearly all pulsars, with characteristic timescales comparable to or even shorter than the average spacing between observ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
80
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 101 publications
(86 citation statements)
references
References 40 publications
6
80
0
Order By: Relevance
“…We used an F-test described by Arzoumanian et al (2015) to determine if new parameters should be added but none were found to be significant. Figure 2 shows the Dt 2,1400 ∝ν −2 timeseries modeled by our step-wise DM model and the trajectory of the pulsar across the sky, with decreasing values shown by darker colors, similar to the depiction in Jones et al (2017).…”
Section: Traditional Timing Model Fitting With Per-epoch Dm Variationmentioning
confidence: 83%
See 3 more Smart Citations
“…We used an F-test described by Arzoumanian et al (2015) to determine if new parameters should be added but none were found to be significant. Figure 2 shows the Dt 2,1400 ∝ν −2 timeseries modeled by our step-wise DM model and the trajectory of the pulsar across the sky, with decreasing values shown by darker colors, similar to the depiction in Jones et al (2017).…”
Section: Traditional Timing Model Fitting With Per-epoch Dm Variationmentioning
confidence: 83%
“…The DDMtimeseries can show dips as seen in Section 7.2 of Lam et al (2016b;see Figure 9 of that paper) if the pulsar moves through both local high-and low-density structures oriented in specific ways along the LOS. Looking at the timescale t for the events to recover by DDM≈ 6×10 −4 pc cm −3 to their initial values after approximately 100-200 days, the local~D~-( ) -n v t DM 10 20 cm e p 3 , a large value for the ISM (Draine 2011) but one that is marginally consistent with the value estimated for PSRJ1909−3744 and possibly PSRJ1738+0333 (Lam et al 2016b;Jones et al 2017). Since the pulsar's 3D velocity v p is not known, we first assumed above that the pulsar moves purely radially toward the Earth (to produce a negative DDM) with a fiducial velocity v p,P = 100 km s −1 and ignored the contribution of the Sun's motion through its own local environment; for reference, note that the pulsar's transverse velocity is v p,⊥ =36.4 km s −1 , estimated from the parallax and proper motion.…”
Section: Local Structurementioning
confidence: 86%
See 2 more Smart Citations
“…Similarly, we could obtain a better estimate of the galaxy merger rate and the population of supermassive black hole binaries in the Universe [8]. PTAs also provide an opportunity to test the theory of gravitation in nanohertz regime [9] Besides gravitational waves detection, other applications of PTAs include providing time standard for long time scales and measurement of solar system ephemerides [10] and a better understanding of the properties of the interstellar medium [11]. The theory of detection of the gravitational wave using PTA is discussed in Sec.II, possible sources of gravitational wave detectable by PTAs are discussed in Sec.III and Sec.IV is the concluding remark with the present status of PTAs and their future targets.…”
Section: Introductionmentioning
confidence: 99%